Instrumentation for ground vibration and earthquakes proceedings of the conference of the Society for Earthquake and Civil Engineering Dynamics held in Keele on 4 and 5 July, 1977. (Institution of Civil Engineers, 1978)
These papers provide a general review of the instrumentation used for recording ground vibration, and the use of vibration monitoring on offshore structures. Some of the papers investigate earth tremors at Stoke-on-Trent, and highlight the effects of vibrations on buildings and on occupants.